Religious Diversity in Singapore (Institure of Southeast Asian Studies, 2008)
This book offers a rich feast of information and ideas on the tremendous religion diversity that exists in Singapore. It revelas the complex challenges facing a secular state that seeks to balance that diversity with the demands of national unity. Putting together a book of this sort is no mean achievement. The credit for this should go to Dr. Lai Ah Eng and the contributors.